Several domination numbers of a complete multipartite graph - Zhao, Yancai,; Shan, Erfang,; Zhao, Weiliang, (Utilitas Mathematica, 2010)
Let γs(G),γ-(G),γt -(G), γt- (G) be the signed domination number, minus domination number, signed total domination number, minus total domination number of a graph G, respectively. The exact values of all the above domination parameters for a complete bipartite graph have been given. In this paper, we provide the exact values of these parameters for a complete multipartite graph.